Estudo da produção de bioetanol e biobutanol a partir da palha de cana-de-açúcar - Pratto, Bruna (2019)
The present thesis studied the hydrolysis and fermentation steps of the hydrothermally pretreated sugarcane straw (cellulosic fraction), aiming bioethanol and biobutanol production. In regards to the hydrolysis step, it is of paramount importance obtaining high glucose concentrations for a feasible bioethanol production. On the other hand, finding an overall efficient process may be challenging since criteria as yield and productivity, may be conflicting sometimes. Thus, a multi-criteria optimization was applied in order to find a balance between yield and productivity in the bioethanol production via pre-saccharification (PS) followed by saccharification and simultaneous fermentation (SSF). PS experiments were carried out evaluating effects of enzymatic dosage, biomass loading, and PS time. After each PS assay, SSF step was run for 24 h. The performance of the whole process (PS + SSF) was evaluated based on overall ethanol yield and productivity. Under optimized conditions, operating in a high solid loading (19.3% w/v), it was possible to obtain an ethanol concentration of 5.6% v/v in a short total processing time of 45 h (hydrolysis + fermentation), which corresponds to approximately 290 L of ethanol per tonne of pretreated sugarcane straw. Also, in the enzymatic hydrolysis step, and as an alternative to the batch PS process, it was studied the fed-batch operation feeding substrate and enzyme, with a total of 21 % w/v of solid load. The suggested feeding policy in this study took into account feeding of substrate and enzyme in a way that the substrate concentration was maintained constant and the reaction rate was maintained equal to or higher than 70 % of the initial hydrolysis reaction rate. In the optimum feeding profile, it was possible to achieve a glucose concentration of 160 g/L, which corresponds to 80 % of cellulose-to-glucose conversion. In addition, it was verified that the non-complete conversion is associated with the non-productive enzyme adsorption, as well as the presence of recalcitrant cellulose. Finally, the thesis also evaluated the potential of biobutanol production by means of ABE (acetone-butanol-ethanol) fermentation using the same biomass. Two hydrolysis-fermentation strategies (SHF - separated hydrolysis and fermentation and PSSSF - pre-saccharification followed by simultaneous saccharification and fermentation), and two biomass concentrations (10 and 15 % w/v) were evaluated. For both strategies, the 10 % w/v concentration was more favorable (~ 4 times higher) with respect to the ABE production, once there was no need to include a detoxification step. Comparing both strategies, the PSSSF achieved a slightly higher ABE production (10.5 g/L to 13.5 g/L) and 60 % higher productivity. In the best condition (10 % w/v - PSSSF), it would be possible to estimate an yield of 170 L of ABE per tonne of pretreated sugarcane straw, corresponding to 65 L of acetone, 95 L of butanol and 10 L of ethanol.